A COMPARATIVE-STUDY OF VARIOUS BIOSORBENTS FOR REMOVAL OF CHROMIUM(VI) IONS FROM INDUSTRIAL-WASTE WATERS - NOURBAKHSH, M; SAG, Y; OZER, D; AKSU, Z; KUTSAL, T; CAGLAR, A (Elsevier Sci Ltd, 1994)
Chromium(VI) biosorption to non-living biomass of Chlorella vulgaris, Clodophara crispata, Zoogloea ramigera, Rhizopus arrhizus and Saccharomyces cerevisiae was investigated The initial pH of the metal ion solution effected metal uptake capacity of the biomass and the optimum initial pH was found as 1.0-2.0 for all microorganisms. Maximum adsorption rates of metal ions to microbial biomass were obtained at temperatures in the range 25-35-degrees-C. The adsorption rate increased with increasing metal ion concentration for C. vulgaris, C. crispata, R. Arrhizus, S. cerevisiae and Z. ramigera up to 200, 200, 125, 100 and 75 mg/litre, respectively. Freundlich constants were determined from the Freundlich adsorption isotherms of all microorganisms.
Keywords: Biosorption; Ramigera